2006
DOI: 10.1097/01.ta.0000204416.33554.0b
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Missile Tract and Intrapericardial Foreign Body with Computed Tomography: Case Report and Review of the Literature

Abstract: enetrating chest injuries involving the heart and great vessels are associated with high morbidity and require rapid determination of the anatomic compartment(s) involved to guide urgent therapy. The decision to explore the mediastinum and cardiac structures is often based on clinical signs, but cardiac penetration may occur without acute hemodynamic compromise or hemopericardium. We describe a case of a hemodynamically stable patient who presented to the emergency department (ED) after projectile lawn mower i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Radiography, echocardiography (ie, transthoracic and esophageal), fluoroscopy, and computed tomography (CT) are useful for localizing cardiac foreign bodies . Accurate localization of pericardial, myocardial, and intrachamber foreign bodies is essential to help guide appropriate intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiography, echocardiography (ie, transthoracic and esophageal), fluoroscopy, and computed tomography (CT) are useful for localizing cardiac foreign bodies . Accurate localization of pericardial, myocardial, and intrachamber foreign bodies is essential to help guide appropriate intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Projectile metallic foreign bodies that remain free in the thoracic cavity are thought to be less likely to cause major complications . Similarly, postsurgical complications associated with the pericardectomy itself are rare …”
Section: Discussionmentioning
confidence: 99%
“…Radiology in the form of plain chest X ray and fluoroscopy can be helpful but in the present era CT angiography and transthoracic echocardiography are the investigations of choice for bullet localization. 8,9 Both AP and lateral chest X ray views obtained in our patient failed to reveal the metallic bullet probably because of overlapping by cardiac shadow and vertebral column. Oblique chest X ray views which might have been beneficial were not obtained in our case as it was felt that a CT scan would still be required to localize exact position and to exclude associated cardiac injuries that might alter therapeutic management.…”
Section: Discussionmentioning
confidence: 55%
“…Studies showed that TTE provides information regarding the size, and location of cardiac foreign bodies with almost 100% sensitivity 8 . Moreover, TEE is a favorable imaging modality in assessing functional and structural damage of the heart, especially in the unstable patient 9 . It was important to note that the foreign body may migrate with blood flow, gravity, or through the myocardial tissues along with the systolic and diastolic beat of heart, resulting in location changes.…”
Section: Discussionmentioning
confidence: 99%